On Option Pricing Bounds - RITCHKEN, PETER H. (Journal of Finance, 1985)
ABSTRACT The purpose of this article is to compare the Perrakis and Ryan bounds of option prices in a single‐period model with option bounds derived using linear programming. It is shown that the upper bounds are identical but that the lower bounds are different. A comparison of these bounds, together with Merton's bounds and the Black‐Scholes prices in a lognormal securities market, is presented.